Penerapan Metode Time Cost Trade Off untuk Optimasi Biaya dan Waktu pada Pengaruh Redesign Struktur Bawah (Studi Kasus: Proyek Pembangunan Klinik Utama Mata Jec Java @Pasuruan Tahap 1) - Doris Zhaputro, Moch. Aldy; Darjanto, Helmy; Conytin Nugrahini, Fibria (Universitas Muhammadiyah Surabaya Publishing, 2024)
ABSTRACT An implementation period of construction projects would usually often experience the risk of delays in the project schedule. It can be caused by various obstacles that occur in the field even though the project has begun with careful planning and scheduling. The delay has a direct result in increasing the duration of implementation and also the cost of implementing the project. One way to overcome these delays is to implement acceleration in implementation so that the project can achieve the target as planned. However, it must also be accompanied by consideration of financing factors in order to achieve minimum costs with quality standards that remain achieved. This acceleration can be done, one of which is by adding working hours (overtime). This research took a case study on the construction project of the JEC Java @Pasuruan Eye Clinic Main Clinic Building which experienced obstacles in foundation work, causing delays in project implementation. To overcome the problem of delay, the acceleration of the time needed would be calculated. The method that will be used is the Time Cost Trade-Off, in which the duration of the work is compressed to get a more profitable project implementation period in terms of time (duration), cost, and income. This research implemented the Crashing Program by using an alternative method of adding working hours (overtime). Crashing was carried out on a critical trajectory obtained from the results of network planning analysis in Microsoft Project 2016. The results showed that by applying the Time Cost Trade-Off method with the alternative of adding 4 hours of work (overtime), the optimal duration of the project was 91 days with an optimal cost of Rp 2,072,972,561. Keywords: Time Cost Trade-Off, Program Crashing, Addition of Working Hours.